Effective modern C++ : 42 specific ways to improve your use of C++11 and C++14 - Meyers, Scott, ....- (Beijing : O'Reilly, 2015)
"Coming to grips with C++11 and C++14 is more than a matter of familiarizing yourself with the features they introduce (e.g., auto type declarations, move semantics, lambda expressions, and concurrency support). The challenge is learning to use those features effectively -- so that your software is correct, efficient, maintainable, and portable. That's where this practical book comes in. It describes how to write truly great software using C++11 and C++14 -- i.e. using modern C++ ...Effective Modern C++ follows the proven guideline-based, example-driven format of Scott Meyers' earlier books, but covers entirely new material"--Publisher's website.
Deducing types -- auto -- Moving to Modern C++ -- Smart pointers -- Rvalue references, move semantics, and perfect forwarding -- Lambda expressions -- The concurrency API -- Tweaks.
Includes index.
Keywords: C++ (Computer program language).; Langages de programmation; Programmation informatique; C++ (Computer program language).